Performance of intercrops in castor-based cropping systems under different tillage practices: Performance of intercrops in castor-based cropping systems under different tillage practices - R SAI MITHRA; G SURESH; K BHANU REKHA; MD A AZIZ QURESHI (Journal of Oilseeds Research, 2023)
Performance of intercrops viz., redgram, greengram and groundnut in castor-based cropping systems under different tillage practices were assessed. Redgram (1616 kg /ha) and greengram (595 kg /ha) recorded highest yield in conventional tillage whereas groundnut (958 kg /ha) recorded highest yield in zero tillage.